Benefactive and Malefactive Verb Extensions in the Koalib Verb System - (:unkn) unknown (My University, 2010)
In Koalib (Niger-Congo, Kordofanian branch, Heiban family), a basic verb can give rise to several verb extensions (VE), among which a benefactive and a malefactive. Section one deals with the main derivational characteristics (affixation, tonology, productivity, valency) of both VE. Section two proposes a more in-depth scrutiny of the morphology of those extensions in Koalib, examining various particular cases (lack of basic verb, double derivation, irregularities). Section three focuses on the semantics of Koalib bene-/malefactive VE, putting special emphasis on the semantic roles encoded by each extension, and on the diverse nuances of meaning they can convey. The conclusion lays the stress on the interest of Koalib (and more generally Kordofanian languages) data for typological studies of the notions of benefaction and malefaction in human language.
Keywords: African Research